Cerebral Venous Thrombosis Mimicking a Discrete Brain Mass: A Case Report and Literature Review - Dana DiRenzo; Zsuzsanna H. McMahan; Naman S. Desai; Rebecca Manno; Michelle Petri (Case Reports in Rheumatology)
The differential diagnosis for a focal brain lesion in a patient with systemic lupus erythematosus (SLE) is broad and includes infection, malignancy, and vascular and inflammatory etiologies. One rarely considered vascular pathology is cerebral venous thrombosis (CVT), which is often associated with a delay in diagnosis because of variable presentation and rare incidence. We present the case of a young woman with a new discrete brain lesion that appeared in the context of highly active SLE and was ultimately diagnosed with a CVT. We provide a literature review for diagnosis and management of cerebral venous thrombosis, a potentially serious complication of untreated systemic lupus erythematosus.